Urban digital economy, environmental pollution, and resident’s health–empirical evidence from China - Zhu, Chen; Wang, Zekai; Sun, Bin; Yue, Yuanyuan (Frontiers in Public Health, 2023)
In light of China's rapid advancement in the digital economy and the implementation of the "Healthy China" initiative, it is crucial to assess the impact of the digital economy on residents' health. This study analyzes data from the 2012, 2014, and 2016 China Labor Force Dynamics Survey (CLDS) to evaluate the health of residents using both subjective and objective criteria. Furthermore, it calculates the digital economy development index for Chinese cities and investigates its influence on the subjective and objective health of residents, along with the underlying mechanisms. The empirical results reveal a U-shaped pattern in the effect of the digital economy on health levels, initially detrimental but subsequently beneficial. The analysis of mechanisms shows that the digital economy's development initially increases and then decreases environmental pollution, impacting health through environmental changes. Additionally, the study finds variations in this impact based on age and urban-rural differences, with more pronounced effects on rural and elderly populations, who also experience the U-shaped curve's turning point more rapidly. These findings highlight the necessity of advancing digital economy infrastructure to positively influence environmental quality and improve public health. The study emphasizes the urgent need for policymakers to invest in digital infrastructure to foster a sustainable and healthy future. This requires a holistic approach to development, focusing on both urban and rural areas, to promote inclusive growth and reduce the digital divide..